2021
DOI: 10.3390/cancers13051019
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Dynamic 18F-FDG PET/CT in Survival Prediction of Metastatic Melanoma under PD-1 Inhibitors

Abstract: The advent of novel immune checkpoint inhibitors has led to unprecedented survival rates in advanced melanoma. At the same time, it has raised relevant challenges in the interpretation of treatment response by conventional imaging approaches. In the present prospective study, we explored the predictive role of quantitative, dynamic 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) performed early during immunotherapy in metastatic melanoma patients receiving treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
0
8
2
Order By: Relevance
“…This finding is consistent with recently published literature investigating spleen metabolism by means of 18 F-FDG PET, which highlighted the significant association between a high SLR and a poor outcome to immunotherapy [ 23 , 49 ]. At the same time, these results should be interpreted with caution, since other studies in the field—although not explicitly involving SLR calculations—have shown a less contributory role of spleen metabolism in differentiating responders from non-responders to ICIs [ 46 , 50 , 51 ], supporting the opinion that spleen metabolism is a “double-edged” biomarker with debatable results [ 52 ]. On the whole, the investigation by means of functional imaging not only of the tumor but also of the patient’s host immune system gradually gains significance as potential surrogate marker of treatment response.…”
Section: Discussionmentioning
confidence: 73%
“…This finding is consistent with recently published literature investigating spleen metabolism by means of 18 F-FDG PET, which highlighted the significant association between a high SLR and a poor outcome to immunotherapy [ 23 , 49 ]. At the same time, these results should be interpreted with caution, since other studies in the field—although not explicitly involving SLR calculations—have shown a less contributory role of spleen metabolism in differentiating responders from non-responders to ICIs [ 46 , 50 , 51 ], supporting the opinion that spleen metabolism is a “double-edged” biomarker with debatable results [ 52 ]. On the whole, the investigation by means of functional imaging not only of the tumor but also of the patient’s host immune system gradually gains significance as potential surrogate marker of treatment response.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, it is of foremost importance to promptly identify subjects who can benefit from such a therapeutic regimen. 18 F-FDG PET/CT, particularly when specific technical approaches such as dynamic acquisition and analysis of PET-derived parameters are utilized, proved useful to predict MM's response to IT and offers the unique opportunity to get an insight into tumor's biology at a molecular level [4][5][6]. To the best of our knowledge, our case is the first report describing diffuse pancreatic metastatic involvement from MM, evaluated before and after IT through PET/CT imaging.…”
Section: Editormentioning
confidence: 91%
“…For example, a prospective study using dynamic 18F-fluorodeoxyglucose positron emission tomography and computed tomography imaging during early phases of systemic ICI in patients with advanced melanoma provided clinical impacts on PFS on the basis of several semiquantitative and quantitative parameters. 177 Additional efforts in examining such an approach may provide further insights into these PFS trends with simultaneous improvements in monitoring treatment responses and guiding therapeutic decisions within this patient population.…”
Section: Novel Approaches and Future Clinical Considerationsmentioning
confidence: 99%